Odpowiedzi

Najlepsza Odpowiedź!
2010-04-06T13:11:07+02:00
H= a√3÷2
a) h=12√3÷2=6√3
b) h=5√3÷2=2,5√3
c) h=√3×√3÷2=3÷2=1,5
d) h=4√18÷2=2√18=6√2

P= a²√3÷4
a) P=64√3÷4=16√3
b) P=100√3÷4=25√3
c) P=12√3÷4=3√3
d) P=50√3÷4=12,5√3
  • Użytkownik Zadane
2010-04-06T13:15:20+02:00
1.
h=a√3/2
h=12√3/2
h=6√3


h=a√3/2
h=5√3/2
h=2,5√3


h=a√3/2
h=√3*√3/2
h=3/2


h=a√3/2
h=4√6*√3/2
h=4√18/2
h=4√9*2/2
h=12√2/2
h=6√2

2.
P=a²√3/4
P=8²√3/4
P=64√3/4
P=16√3

P=a²√3/4
P=10²√3/4
P=100√3/4
P=25√3

P=a²√3/4
P=(2√3)²√3/4
P=12√3/4
P=3√3

P=a²√3/4
P=(5√2)²√3/4
P=50√3/4
P=12,5√3